Redesigning a community-based challenging behaviour intensive support service. Issue 3 (12th June 2019) - White, Jasmin; Symes, Matt; Pearce, Carrie
Abstract : Purpose: The purpose of this paper is to discuss outcomes of a service redesign, involving an Intensive Support Team (IST) for adults with learning disabilities and challenging behaviour, working in conjunction with a Community Learning Disability Service (CLDS). Design/methodology/approach: Two IST staff were physically based as "Inreach workers" within a CLDS for six months. Inreach workers provided support with existing resources and consultation for specific clients presenting with challenging behaviour. CLDS staff confidence, understanding and implementation of existing challenging behaviour resources was evaluated before and after service redesign. An online questionnaire was used to gather further data relating to experiences of the Inreach project. Findings: CLDS staff confidence, understanding and implementation of existing challenging behaviour resources increased over the six-month inreach period. Questionnaire results indicated CLDS staff found Inreach support to be beneficial, having a perceived positive impact for clients, and providing clarity on the skills and resources provided by the IST. Research limitations/implications: The long-term effects of this pilot have yet to be established. Consideration is given to how demand characteristics may have influenced CLDS responses. Practical implications: Careful consideration should be given in terms of how ISTs interface with CLDSs. ISTs may consider being based physically within CLDSs, to provide more readily accessible support. Originality/value: Providing CLDS staff with more accessible support from ISTs may increase the effective implementation of available resources for adults with learning disabilities and challenging behaviour.